2007
DOI: 10.1038/sj.onc.1210429
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer specific integrin αvβ3 modulates bone metastatic growth and tissue remodeling

Abstract: The management of pain and morbidity due to the spreading and growth of cancer within bone remains to be a paramount problem in clinical care. Cancer cells actively transform bone, however, the molecular requirements and mechanisms of this process remain unclear. This study shows that functional modulation of the avb3 integrin receptor in prostate cancer cells is required for progression within bone and determines tumor-induced bone tissue transformation. Using histology and quantitative microCT analysis, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
139
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(144 citation statements)
references
References 23 publications
5
139
0
Order By: Relevance
“…It has been reported that ␣ v ␤ 3 -integrin is associated with malignancy and invasion of primary prostate cancer cells (51). Our results demonstrate that the specific inhibition of CtsH promotes the activation of ␣ v ␤ 3 -integrin on migrating PC-3 cells.…”
Section: Discussionsupporting
confidence: 63%
“…It has been reported that ␣ v ␤ 3 -integrin is associated with malignancy and invasion of primary prostate cancer cells (51). Our results demonstrate that the specific inhibition of CtsH promotes the activation of ␣ v ␤ 3 -integrin on migrating PC-3 cells.…”
Section: Discussionsupporting
confidence: 63%
“…The basal cell profile was consistent with a proliferative phenotype, with expression of CXCL1, NBS1 and RPA, all of which encode proteins shown earlier to promote proliferation (Chiang et al, 2003;Li et al, 2004;Givalos et al, 2007). The expression of aV integrin has earlier been described in metastatic prostate cancer (McCabe et al, 2007) but not in benign prostate cells, where it may have a role in adhesion to the basement membrane.…”
Section: Discussionmentioning
confidence: 53%
“…These lesions are osteoblastic or osteolytic and are frequently detected in prostate cancer patients (over 80% of prostate cancer patients have established bone metastasis at autopsy (Koeneman et al 1999)). A recent study has shown that the a v b 3 integrin promotes bone gain mediated by prostate cancer cells that metastatize to the bone and point to a v b 3 as a potential therapeutic target to block prostate cancer osteoblastic lesions (Keller & Brown 2004, McCabe et al 2007. Besides therapeutic applications, other uses of integrin inhibitors are in the area of imaging and specific delivery of a drug to cancer cells (Chen et al 2001, Moschos et al 2007, Li et al 2008.…”
Section: Discussionmentioning
confidence: 99%